DANDY-WALKER MALFORMATION (DWM): CASE REPORT OF A DELAYED PRESENTATION - Usman B; Mohammed B (Ntec Specialist, 2018)
Background: Dandy-Walker Malformation (DWM); a group of posterior fossa malformation characterized by a cystic enlargement of posterior fossa with high lying torcula herophili (fetal position) and a hypoplastic vermis pushed and rotated superiorly by the cyst occurs in 1 in 25,000 - 35,000 live birth and accounts for 1 - 4 % of all Hydrocephalus seen within 3 months of birth. Case report: An 8-year-old girl from an orphanage who presented with a history of progressive head enlargement, delayed developmental milestones and poor vision. No history suggestive of raised intracranial pressure, differential limb weakness or associated congenital systemic anomalies. All fontanelles were fused. Muscle power was normal, globally spastic with brisk deep tendon reflexes. The eye examination revealed bilateral light perception only. Brain CT Scan revealed a large posterior fossa cyst, hydrocephalus and corpus callosum hypoplasia. The patient had a double shunt (ventriculoperitoneal and cysto - peritoneal). Currently on rehabilitation and can count fingers. Conclusion: Early identification and prompt intervention minimizes the neurological sequelae